2024
DOI: 10.1111/acel.14051
|View full text |Cite
|
Sign up to set email alerts
|

Long term methionine restriction: Influence on gut microbiome and metabolic characteristics

Akash Nagarajan,
Alexander Tate Lasher,
Casey D. Morrow
et al.

Abstract: The Methionine restriction (MR) diet has been shown to delay aging and extend lifespan in various model organisms. However, the long‐term effects of MR diet on the gut microbiome composition remain unclear. To study this, male mice were started on MR and control diet regimens at 6 months and continued until 22 months of age. MR mice have reduced body weight, fat mass percentage, and bone mineral density while having increased lean mass percentage. MR mice also have increased insulin sensitivity along with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…It has been reported recently that Ileibacterium valens promotes intestinal inflammation and tumorigenesis in colorectal cancer [40,41]. Previous research indicated that the abundance of Marinifilaceae increased in mice fed with a long-term methionine restriction diet [42]. Turicibacter was abundantly detected in tumor-bearing mice [43].…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported recently that Ileibacterium valens promotes intestinal inflammation and tumorigenesis in colorectal cancer [40,41]. Previous research indicated that the abundance of Marinifilaceae increased in mice fed with a long-term methionine restriction diet [42]. Turicibacter was abundantly detected in tumor-bearing mice [43].…”
Section: Discussionmentioning
confidence: 96%